The Recent Applications of PLGA-Based Nanostructures for Ischemic Stroke - Jun Yan; Lei Huang; Juan Feng; Xue Yang (MDPI AG, 2023)
With the accelerated development of nanotechnology in recent years, nanomaterials have become increasingly prevalent in the medical field. The poly (lactic acid-glycolic acid) copolymer (PLGA) is one of the most commonly used biodegradable polymers. It is biocompatible and can be fabricated into various nanostructures, depending on requirements. Ischemic stroke is a common, disabling, and fatal illness that burdens society. There is a need for further improvement in the diagnosis and treatment of this disease. PLGA-based nanostructures can facilitate therapeutic compounds' passage through the physicochemical barrier. They further provide both sustained and controlled release of therapeutic compounds when loaded with drugs for the treatment of ischemic stroke. The clinical significance and potential of PLGA-based nanostructures can also be seen in their applications in cell transplantation and imaging diagnostics of ischemic stroke. This paper summarizes the synthesis and properties of PLGA and reviews in detail the recent applications of PLGA-based nanostructures for drug delivery, disease therapy, cell transplantation, and the imaging diagnosis of ischemic stroke.